Causes of Intrauterine Fetal Death during COVID-19 outbreak in a Tertiary Care Hospital in Lahore, Pakistan - Mahwish Saif , Arfa Bin Saqib, (Journal of Rawalpindi Medical College, 2021)
Objective: To assess the frequency of IUDs and their possible causes since the Covid-19 pandemic. Material and Methods: Study design: Cross-sectional study Setting: Department of Obstetrics and Gynaecology, Shalamar Hospital, Medical and Dental College, Lahore, Pakistan. Duration of study: 15/03/2020 to 15/06/2020 This is a cross-sectional single-center study. The relevant details about IUDs like age, parity, social status, booked status, comorbidities, and social status were entered into a Performa and the data analyzed. Results: The Intrauterine death rate from the study was 41.99 fetal deaths per 1000 live births (Total births: 643, IUDs: 27) while the mean age of the mothers was 29.67 with a minimum age of 22 years and a maximum of 37 years. According to the risk factors associated with the IUD, 11.1% had Pregnancy Induced hypertension, 11.1% had Pre-Eclampsia, 22.2% had Gestational Diabetes Mellitus and 22.2% Pregnancy Induced Hypertension and Gestational Diabetes Mellitus and 33.3% had no comorbidities. Amongst all the patients 33.3% of cases were unbooked. Conclusion: We conclude that in the last one year the fetal deaths per 1000 at Shalamar Hospital were around 28.57 per 1000 live births, during the last 3 months they gone up to 41.99 fetal deaths per 1000 live births. The leading cause(s) for IUDs in Pregnancy during the Covid-19 were pandemic Induced Hypertension and Gestational Diabetes Mellitus, which cumulatively account for 44.4% cases but 33.3% cases had no co-morbidities and still ended up in an Intra-Uterine death, which may or may not have been influenced by a Covid-19 infection. From the looks of it, Non-clinical reasons seem to have a higher probability of increasing the IUD rate but clinical effects of the Covid-19 infection can also not be ruled out completely, further studies are required into the pathogenesis and the effect of Covid-19 on pregnancy.